IMPLEMENTASI PENDIDIKAN AG AMA DAN KEAGAMAAN PASCA KONFLIK DI POSO SULAWESI TENGAH - Amiruddin Amiruddin (Al-Qalam, 2008)
This research aims to describe the implication of social conflict to educationof religion (formal and informal) implementation. This was conductedat Poso, Midle Sulawesi. Data was collected by depth interviewand observation.This research indicates that social conflict atAralle, Tabulahan, Mambiduring 2002-2005 had give impact the some education of religion implementation,such as (a) number of teachers and students was decrease.Most of them went out to another place; (b). Some students have differentperspective after this conclict, for example; several students denylearning English, because it s non-Moslem language.Local government regulate a lot ofprogram to heal this effect of conflict,such as (a) empowering religion organization (Muhammadiyah, NUetc) to take active role; (b) facilitating dialog between moslem andChrist people